2019
DOI: 10.1080/12298093.2019.1635425
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activities of Streptomyces blastmyceticus Strain 12-6 Against Plant Pathogenic Fungi

Abstract: Streptomyces blastmyceticus strain 12-6 was isolated from a forest soil sample of Cheonan area on the basis of strong antifungal activities against plant pathogenic fungi. Butanol extracts of the cultural filtrates were active against C. acutatum, C. coccodes, C. gloeosporioides, F. oxysporum, and T. roseum. Active fractions were prepared by thin layer chromatography using silica gel plate; 12-6-2 (Rf 0.36), 12-6-3 (Rf 0.44). Scanning electron microscopy showed that the active fractions caused a change in surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 17 publications
4
19
0
1
Order By: Relevance
“…Often, these rhizospheric microbes individually or in consortia produce a wide variety of secondary metabolites that are known to aid in plant growth under stressful conditions (Musilova et al 2016). Inhibition of M. phaseolina growth by these Streptomyces strains is mainly attributed to their ability to produce anti-fungal compounds such as hydrolytic enzymes and acids (Alekhya and Gopalakrishnan 2017;Vijayabharathi et al 2018;Kim et al 2019). These PGPR strains are mainly regarded as bio-control agents as they potentially produce chitinase, siderophore and hydrocyanic acid (HCN) which confer disease resistance in crops such as wheat (Kumar et al 2018) and tomato (Abo-Elyousr et al in the present study were previously reported to produce chitinase, siderophore and HCN (Gopalakrishnan et al 2011a;Sreevidya et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Often, these rhizospheric microbes individually or in consortia produce a wide variety of secondary metabolites that are known to aid in plant growth under stressful conditions (Musilova et al 2016). Inhibition of M. phaseolina growth by these Streptomyces strains is mainly attributed to their ability to produce anti-fungal compounds such as hydrolytic enzymes and acids (Alekhya and Gopalakrishnan 2017;Vijayabharathi et al 2018;Kim et al 2019). These PGPR strains are mainly regarded as bio-control agents as they potentially produce chitinase, siderophore and hydrocyanic acid (HCN) which confer disease resistance in crops such as wheat (Kumar et al 2018) and tomato (Abo-Elyousr et al in the present study were previously reported to produce chitinase, siderophore and HCN (Gopalakrishnan et al 2011a;Sreevidya et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was confirmed in the secondary metabolite production assay as the organic fraction of the culture filtrate of CAI-21 inhibited M. phaseolina by 73.8% (Table 1 and Figure 2). Inhibition of M. phaseolina growth by PGP microbial strains is mainly attributed to their ability to produce antifungal compounds such as hydrolytic enzymes (cellulase and chitinase) and hydrocyanic acids (HCN) [24,25]. Plant growth-promoting rhizobacteria (PGPR) strains are mainly regarded as biocontrol agents as they potentially produce siderophores, chitinase, and HCN, which induce disease resistance in agriculturally important crops [26,27].…”
Section: In Vitro Inhibitory Activity Of S Albus Cai-21mentioning
confidence: 99%
“…PGPR especially, the For HCN production, the following rating scale was used: 0 ¼ no colour change; 1 ¼ light reddish brown; 2 ¼ medium reddish brown; and 3 ¼ dark reddish brown Streptomyces spp. produce various hydrolytic enzymes and acids that show antifungal ability against different agriculturally important fungal pathogens (Alekhya and Gopalakrishnan 2017;Vijayabharathi et al 2018;Kim et al 2019;. This PGPR-plant interaction also enhances the jasmonic acid, salicylic acid and ethylene production, which in turn activates the induced and systemic acquired resistance to subdue the disease (Vleesschauwer and Höfte 2009).…”
Section: Role Of Pgpr As Biocontrol Agentsmentioning
confidence: 99%
“…During recent years, several research studies have reported the significance of rhizosphere microbes in playing an important role in the plant growth promotion, in formation of important microbial consortia and disease resistance in host plants (Bhattacharyya and Jha 2012;Alekhya and Gopalakrishnan 2017;Vijayabharathi et al 2018;Anusha et al 2019;Gopalakrishnan and Vadlamudi 2019;Kim et al 2019). Also, they emerged as a potential alternative for chemical fertilizers and have shown promising crop yield outputs in agricultural fields (Laslo and Mara 2019).…”
Section: Introductionmentioning
confidence: 99%